Sikap dan Niat Beli Kosmetik Halal : Systematic Literature Review 2015-2025 - Risa Rahmawati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The halal cosmetics industry has experienced significant growth alongside increasing awareness among Muslim consumers of products that are safe and compliant with religious values. However, empirical findings on the influence of knowledge and religiosity on attitudes and purchase intention toward halal cosmetics remain fragmented and inconsistent. Therefore, this study aims to systematically synthesize research trends, dominant findings, and empirical evidence regarding the relationships among knowledge, religiosity, attitude, and purchase intention in the context of halal cosmetics. A Systematic Literature Review (SLR) was conducted on 25 scholarly articles selected based on predefined inclusion criteria and analyzed using the PRISMA framework. The review focuses on research trends, dominant variables, methodological approaches, and the mechanisms linking the studied constructs. The findings indicate that religiosity is the most consistent determinant influencing consumer attitudes and purchase intention toward halal cosmetics, whereas the effect of halal knowledge varies depending on consumers’ halal literacy and risk perception. Moreover, consumer attitude plays a crucial mediating role between knowledge, religiosity, and purchase intention. Overall, this study highlights the central role of attitude in explaining halal cosmetics purchase intention and provides theoretical and practical implications for the development of the halal cosmetics industry.